Deletion of a kinesin I motor unmasks a mechanism of homeostatic branching control by neurotrophin-3 - Auer, Thomas; Wittbrodt, Joachim (eLife, 2015)
Different regions of a neuron have distinct structures and roles. For example, each neuron has a cable-like structure called the axon that extends out of the body of the cell and carries electrical signals away from the cell body. To pass these messages on to neighboring cells, branches on the axon form connections called synapses with other neurons. The axon lacks most of the cellular machinery needed to make proteins and other molecules that the cell needs to work correctly. Therefore, neurons must transport these materials from the cell body - where they are produced - down to the end of the axon. Specialized proteins called molecular motors carry this cargo down the axon along ‘tracks’ composed of filaments called microtubules. Auer, Xiao et al. have now used genetic techniques to disrupt the gene that encodes an important molecular motor, called Kif5A, in developing zebrafish larvae. The effects of this manipulation on the development of the zebrafish's visual system were then examined. When zebrafish are a few days old, neurons in the retina - the structure at the back of the eye that responds to light - extend axons into a region of the brain called the tectum. The formation of synapses between cells in the retina and the tectum provides a pathway that enables information to travel from the eye to the brain. Auer, Xiao et al. found that in larvae that lack Kif5A, axons from the retina enter the brain about a day later than they do in normal larvae. However, when these mutant axons arrive, they produce large numbers of branches, each with the potential to form multiple synapses with cells in the tectum. However, none of the resulting synapses appear to respond to visual stimuli, which is consistent with the fact that Kif5A mutant larvae are blind. Experiments to identify what triggers the excessive branching of retinal axons revealed that the mutant fish had elevated levels of a growth-promoting protein called neurotrophin-3 in cells in the tectum. This increased production of neurotrophin-3 was also observed when neuronal activity was blocked, for example by toxins. The lack of neuronal activity in retinal axons therefore seems to increase the production of neurotrophin-3, which in turn stimulates axonal branching. Future experiments could investigate the molecular signal that drives this increased production of neurotrophin-3, and how this is regulated during normal neuronal development.